Seismic resilience of plywood-coupled LVL wall panels. (15th July 2018) - Iqbal, Asif; Fragiacomo, Massimo; Pampanin, Stefano; Buchanan, Andrew
Highlights: Experimental and numerical investigation of wall panels with plywood coupling is described. The specimen has been tested under repeated cyclic loading to simulate more than one seismic event. The walls remain virtually undamaged and energy is dissipated mostly through yielding of nails. Stiffness is reduced after the first cycle due nail yielding but there is no further degradation. With easy replacement of plywood the arrangement reduces downtime due to repair. Abstract: Structural wall panels Laminated veneer lumber (LVL) have been proposed for enhanced seismic resistance of multi-storey timber buildings based on research performed at University of Canterbury, New Zealand. The system is designed to be self-centering with unbonded post-tensioning and dissipate energy through ductile connections. This paper describes the experimental and numerical investigation of one such arrangement with post-tensioned LVL wall panels coupled with plywood sheets. It is observed that energy is dissipated mostly through yielding of the nails used to attach plywood sheets to the wall panels, and whole assembly return close to their initial position while remaining virtually undamaged. The same specimen has been tested under repeated series of cyclic loading to investigate the performance of the arrangement under more than one seismic event (e.g. a major earthquake followed by a significant aftershock). Different nail spacing and arrangements have been tested to compare their energy dissipation characteristics. The results indicate good seismic performance, characterized by negligible damage of the structural members and very small residual deformations. The only component significantly damaged is the nailed connection between the plywood sheet and the LVL wall panels. Although the nails yield and there is a reduction in stiffness, the system exhibits a stable performance without any major degradation throughout the loading regime. After an earthquake, the plywood can be easily removed and replaced with new sheets, which are reasonably cheap and easy to install, allowing for major reduction in downtime. With these additional benefits the concept deserves further considerations as a potentially alternative solution for multi-storey timber buildings.